Location specific temperature compensation of guided wave signals applied to pipe inspections - Mariani,S; Cawley,P (2019)
The baseline subtraction method is widely used to detect defect signatures in guided wave structural health monitoring. In essence, an earlier measurement is subtracted from the 'current' signal, and high residuals might indicate damage occurrence. However, varying environmental and operational conditions, such as temperature, also produce signal changes and hence, potentially, high residuals. A number of temperature compensation methods have been developed, which typically targets the varying wave speed due to varying temperature. Nevertheless, other, subtler effects caused by temperature variations are often overlooked, such as changes in attenuation, in the transducer frequency response and in the relative amplitudes of different modes excited by the transducer. A novel temperature compensation method has been recently presented by the authors, which compensates for temperature induced changes of wave speed and signal phase. The compensated signals can then be fed to a second temperature compensation procedure that has been newly developed. This will correct any spatially dependent signal change that is a systematic function of temperature, hence producing residuals less affected by temperature variations. This new method was applied to a set of T(0,1) guided wave signals collected by a pipe monitoring system, yielding residuals reduced by at least 50% compared to those obtained using the standard approach at positions away from structural features, and by more than 90% at features such as the pipe end. The method therefore promises a substantial improvement in the detectability of small defects, particularly at existing pipe features.